Pemberdayaan Taman Pendidikan Al-Qur’an Sebagai Pusat Pendidikan Karakter Religius - Yogo Bekti Kusuma; Siti Zazak Soraya (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
The development of children's character has changed as the times have changed. Saying politely, respecting parents, and practicing manners appear to be lacking in the character of children today, including children in Selorejo village, Magetan. As a result, the Al-Quran Education Learning Centre (Taman Pendidikan Al-Qur'an) is one way to instill character, particularly religious character. This commmunity service aims to maximize TPA's role in religious character education. Using the Asset Based Community-Driven Development (ABCD) approach, ten elementary school-aged children participated in this activity. The service results show that children understand and practice religious characteristics such as speaking politely, being polite, and beginning activities with bismillah in their daily lives.